2015
DOI: 10.1155/2015/532628
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Durotomy in Minimally Invasive Transforaminal Lumbar Interbody Fusion: Frequency, Risk Factors, and Management

Abstract: Purpose. To assess the frequency, risk factors, and management of accidental durotomy in minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Methods. This single-center study retrospectively investigates 372 patients who underwent MIS TLIF and were mobilized within 24 hours after surgery. The frequency of accidental durotomies, intraoperative closure technique, body mass index, and history of previous surgery was recorded. Results. We identified 32 accidental durotomies in 514 MIS TLIF levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The surgical technique of performing minimally invasive stabilization procedures with screw-rod instrumentation (CD Horizon Sextant II or CD Horizon Longitude, Medtronic, Minneapolis, USA) has been described in detail elsewhere [ 14 ]. For minimally invasive thoracic instrumentation we routinely use intraoperative spinal navigation for accurate screw placement (Cart II system, Stryker, Freiburg, Germany; software: SpineMap 3D navigation) [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The surgical technique of performing minimally invasive stabilization procedures with screw-rod instrumentation (CD Horizon Sextant II or CD Horizon Longitude, Medtronic, Minneapolis, USA) has been described in detail elsewhere [ 14 ]. For minimally invasive thoracic instrumentation we routinely use intraoperative spinal navigation for accurate screw placement (Cart II system, Stryker, Freiburg, Germany; software: SpineMap 3D navigation) [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dural tears occurred in 3.9–6.1% of the patients undergoing MI-TLIF [Tables 3 – 5 ]. [ 20 23 40 ] Wong et al . (2015) found a 5.1% durotomy rate for 513 MI-TLIF.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) noted that for 372 MIS TLIF (514 levels) there were 32 durotomies (6.2%) that highly correlated with more advanced age (e.g., over 65) and obesity. [ 20 ] Liu et al . (2016) found 4 (3.9%) instances of dural tears out of 101 TLIF (101 patients).…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of LLIF involve the placement of a large cage without violating the posterior elements compared with MIS transforaminal interbody fusion (TLIF). Compared to ALIF, there is decreased risk of major artery or visceral injury with intact anterior annulus and ligaments [ 4 , 7 10 ]. It has also been suggested that LLIF can enhance the stability of the anterior column, create substantial indirect decompression with a restored disc and foraminal height, and significantly improve the coronal and sagittal alignment in selected de novo scoliosis cases [ 6 , 11 15 ].…”
Section: Introductionmentioning
confidence: 99%